2020
DOI: 10.1101/2020.07.18.209775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNAseq analysis of rodent spaceflight experiments is confounded by sample collection techniques

Abstract: To understand the physiological changes that occur in response to spaceflight, mice are transported to the International Space Station (ISS) and housed for variable periods of time before euthanasia on-orbit or return to Earth. Sample collection under such difficult conditions introduces confounding factors that need to be identified and addressed. We found large changes in the transcriptome of mouse tissues dissected and preserved on-orbit compared to tissues from mice euthanized on-orbit, preserved, and diss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…As well we combined different controls and ight cohorts to increase our sample size which was not ideal. It is also worth mentioning that previous studies examining physiological changes in mice sent to the ISS found challenges associated with sample collection in space and the confounding factors it introduces [52]. This includes changes in the transcriptome due to preservation methods, which can overshadow differences between space ight and ground samples, suggesting the need for careful consideration of these factors in future space research.…”
Section: Discussionmentioning
confidence: 99%
“…As well we combined different controls and ight cohorts to increase our sample size which was not ideal. It is also worth mentioning that previous studies examining physiological changes in mice sent to the ISS found challenges associated with sample collection in space and the confounding factors it introduces [52]. This includes changes in the transcriptome due to preservation methods, which can overshadow differences between space ight and ground samples, suggesting the need for careful consideration of these factors in future space research.…”
Section: Discussionmentioning
confidence: 99%
“…Most experimentation in space is expensive, time-consuming and not automated. This results in small experiments with few samples and replicates, and high levels of variability due to differing sample-handling procedures [53][54][55] . This makes AI and time in space and distance from Earth 1,6 .…”
Section: Automated Experiments In Space Supported By Aimentioning
confidence: 99%
“…This appeared to be exacerbated by the use of poly(A) enrichment-based RNA sequencing (RNA-seq) protocol, and could be alleviated by the use of a ribodepletion-based approach and by snap-freezing carcasses in liquid nitrogen. 60 As a result, the Rapid Freeze hardware was recently developed for use on the ISS. The device can freeze mouse tissues (Glovebox freezer) and whole carcasses (Cryochiller) at rates similar to those attained with liquid nitrogen immersion.…”
Section: Sample Preservationmentioning
confidence: 99%